Approaches to teaching Tolkien's The Lord of the Rings and other works - Donovan, Leslie A., 1957- (New York : The Modern Language Association of America, 2015)
"Offers pedagogical techniques for teaching Tolkien's The Lord of the Rings, The Hobbit, and The Silmarillion in undergraduate and graduate classes. Topics include race, gender, sources, environmental sustainability, interdisciplinarity, learning communities, science, epic, pastoral, and reception. Includes syllabus suggestions, information on editions, reference works, biographies, film adaptations, and online resources"--
Part One: Materials / Leslie A. Donovan -- Tolkien in context -- Editions -- The instructor's library -- Multimedia aids for teaching -- Part Two: Approaches. Introduction: Seed of courage not so hidden / Leslie A. Donovan -- Teaching the Controversies. The perils of the Tolkien course: reading the readings / Craig Franson -- Teaching the critical debate over The Lord of the Rings / James McNelis -- Tolkien's Other Works as Background. Eucatastrophe and the battle with the dark / Verlyn Flieger -- Why teach The Silmarillion? Tolkien's mythology of the abject hero / Jane Chance -- Child of the kindly west: innocence and experience in The Hobbit / Brian Walter -- Using The History of Middle-earth with Tolkien's fiction / Yvette Kisor -- Connections to the Past. Presenting Tolkien's pasts / Robin Chapman Stacey -- Teaching the oral tradition in The Lord of the Rings / Leslie Stratyner -- Becoming Tolkien: reading his Anglo-Saxon and Boethian sources / Liam Felsen -- Tolkien as nation builder: teaching The Lord of The Rings in an epic literature class / Melissa Ridley Elmes -- Conceptions of the pastoral in The Fellowship of the Ring / Philip Irving Mitchell -- Modern and Contemporary Perspectives. Teaching Tolkien in the context of the fantasy tradition / Christopher Cobb -- Tolkien and the modern: reading the canon through The Lord of the Rings / Sharin Schroeder -- The tower, the sausage maker, and the soup: teaching Tolkien in a postmodern classroom / Thomas L. Martin -- Teaching Tolkien and race: an inconvenient combination? / Dimitra Fimi -- Women students and The Lord of the Rings: showing them where they fit in / Shelley Rees -- Language, culture, environment, and diversity in The Lord of the Rings / Deidre Dawson -- Interdisciplinary Contexts. Starting with the film: Jackson as a way back to Tolkien on heroism and evil / Christopher Crane -- Tolkien and faith: an interdisciplinary approach / Nancy Enright -- Melkor, moon letters, and Menelmacar: Middle-earth in the science classroom / Kristine Larsen -- Tolkien and environmental sustainability in the science curriculum / Justin Edward Everett -- Classroom Contexts and Strategies for Teaching. Tolkien in the first-year literature survey course / Anna Smol -- Team-teaching Tolkien in a large lecture class: challenges and opportunities / Julia Simms Holderness -- England's mythmaker? A Tolkien learning community / James R. Vitullo and Keith W. Jensen -- "(T)hings that were, and things that are, and things that yet may be": teaching Tolkien's The Lord of the Rings online / Judy Ann Ford and Robin Anne Reid -- Morals and malice in Middle-earth / James Gould and Ted Hazelgrove -- Tolkien immersion: why a three-week intensive course works / Cami D. Agan -- The Council of Elrond, all those poems, and the famous f-ing elves: teaching the hard parts of Tolkien / Michael D.C. Drout -- Fellowship and the rings: intellectual sociability and collaborative learning among Tolkien and the Inklings / Michael Tomko.
Includes bibliographical references and indexes.
Keywords: Tolkien, J. R. R. -- 1892-1973 -- Study and teaching; Tolkien, J. R. R. -- 1892-1973 -- Criticism and interpretation; Fantasy fiction, English -- Study and teaching; LANGUAGE ARTS & DISCIPLINES / Study & Teaching; LITERARY CRITICISM / Science Fiction & Fantasy; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh